2019
DOI: 10.1111/jfb.13991
|View full text |Cite
|
Sign up to set email alerts
|

Selection of reference genes for quantitative real‐time PCR normalisation in largemouth bass Micropterus salmoides fed on alternative diets

Abstract: The partial cDNA sequences of eight reference genes (actb, tuba1, gapdh58, gapdh59, eef1a1, RNA 18 s, pabpc1, ube2I) were cloned from largemouth bass Micropterus salmoides. The expression levels of these eight genes were compared in the various tissues (eye, spleen, kidney, gill, muscle, brain, liver, heart, gut and gonad) of M. salmoides fed on forage fish. The results showed that the candidate genes exhibited tissue‐specific expression to various degrees and the stability ranking order was eef1a1 > tuba1 > R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The temperature gradually increased from 65 to 95°C, with 0.5°C every 6 s. According to the instructions of GoTaq® qPCR Master Mix (Bio-Rad, USA), the reaction was composed of 0.2 μM of primers, 1 μl cDNA, 10 and μl GoTaq® qPCR Master Mix and supplied with double-distilled water at 20 μl. The mRNA expression levels were quantified relative to the expression of elongation factor 1 α ( ef1 -α) as endogenous reference ( 20 ) and analyzed by the optimized comparative Ct (2 ΔΔ Ct ) value method ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…The temperature gradually increased from 65 to 95°C, with 0.5°C every 6 s. According to the instructions of GoTaq® qPCR Master Mix (Bio-Rad, USA), the reaction was composed of 0.2 μM of primers, 1 μl cDNA, 10 and μl GoTaq® qPCR Master Mix and supplied with double-distilled water at 20 μl. The mRNA expression levels were quantified relative to the expression of elongation factor 1 α ( ef1 -α) as endogenous reference ( 20 ) and analyzed by the optimized comparative Ct (2 ΔΔ Ct ) value method ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies also indicated that an internal reference gene often has diverse expression levels in different species, different cells or even different experiment conditions. Thus, the selection of a reliable internal reference gene is one of the important factors to detect quantification of the target gene expression analysis by qPCR (Ma et al, 2019). The software of geNorm, NormFinder and BestKeeper can further calculate the values of reference gene expression stability and give comprehensive ranking of reference genes.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR was carried out on a LightCycler ® 480 II instrument (Roche, Basel, Switzerland) using a TB Green ® Premix Ex Taq™ II Kit [48]. The relative mRNA expression levels were calculated using the 2 −∆∆CT method [49], and the β-actin gene of largemouth bass was used as an internal control [50]. The primers used for qRT-PCR are listed in Table S1.…”
Section: Rna Isolation and Qrt-pcr Analysismentioning
confidence: 99%